PEMBENAHAN DAN PENATAAN KAWASAN WISATA ALAM DESA BATU MEKAR, KECAMATAN LINGSAR, KABUPATEN LOMBOK BARAT - Faturahman Faturahman; Muhammad Abdul Haris Ramdan; Sofian Ichsan Muladi; Aprilianing Diah; Mega Puspita Ningsih (Jurnal Abdi Insani, 2022)
Timponan Waterfall Tourism in Batu Mekar Village, Lingsar, West Lombok is one of the natural resources in the form of a waterfall that has the potential to be developed as a tourist attraction. The existence of tourism objects and attractions is the most important link in a tourism activity. This service activity aims to promote tourism, especially Timponan Waterfall, which is the object of tourist attraction in Batu Mekar Village in the form of making signposts, making tourist order boards, making banners and designing promotional videos. This activity uses the Participatory Rural Appreciation (PRA) method in the field from preparation to the end of the activity and to determine priority programs, discussions are held with tourism administrators. The agreed forms of activity are the manufacture of signposts, the manufacture of tourist order boards, the manufacture of banners and the design of promotional videos. The results of this service activity are shown by a very positive response and appreciation from the partner community for participating in this activity from the beginning to the end of the event. The form of activity that has been carried out is the socialization of the importance of developing village tourism destinations, especially natural panorama-based tourism which is the mainstay of Batu Mekar Village, namely the Timponan Waterfall. The physical activities that have been completed according to the mutual agreement are the manufacture and installation of signposts to the Timponan waterfall tourist location, the manufacture and installation of travel rules and regulations, and the manufacture of banners for safe travel in the new normal era. All programs have been implemented well, but further activities are needed, namely making videos to promote tourist attractions.